Functional characterization of ecto-5'-nucleotidases and apyrases in Drosophila melanogaster - Fencková, Michaela; Hobizalová, Radka; Faltýnek, Zdeněk, Fric; Doležal, Tomáš (Insect biochemistry and molecular biology, 2011)
Ecto-5'-nucleotidases are glycosyl phosphatidylinositol (GPI)-linked membrane-bound glycoproteins that convert extracellular AMP to adenosine. They play important roles in the inflammatory response where they modulate levels of pro-inflammatory extracellular ATP and anti-inflammatory extracellular adenosine. They are found in the saliva of blood feeding insects and also have a role in male reproduction. Drosophila possesses five genes with eight alternative transcripts encoding proteins with sequence homology to mammalian ecto-5'-nucleotidases. Here we show that two of them - NT5E-1 (CG4827) and NT5E-2 (CG30104) - are GPI-linked proteins with ecto-5'-nucleotidase activity but that they can also be released from the GPI anchor and exhibit secreted 5'-nucleotidase activity in growth media. The third locus in the cluster, CG30103, most likely also encodes a GPI-anchored membrane-bound protein but without 5'-nucleotidase activity, possibly due to the numerous substitutions in the amino acid sequence. Together with NT5E-2, CG30103 is also expressed in the testis offering an interesting model to investigate ecto-5'-nucleotidase enzymatic and extra-enzymatic function in male reproduction. CG42249 locus encoding two alternative transcripts is sequentially similar to family of apyrases related to 5'-nucleotidases and we show here that together with CG5276 belonging to another family of calcium-activated nucleotidases function as apyrases converting extracellular ATP to ADP and AMP. The last locus, CG11883, encodes most likely a cytoplasmic/mitochondrial protein.
Keywords: 5'-Nucleotidase; Animals; 5'-nukleotidasa; vývojová regulace genové exprese; multigenová rodina; Humans; Gene Expression Regulation, Developmental; Multigene Family; buněčné linie; lidé; zvířata; Drosophila Proteins; Apyrase; molekulární sekvence - údaje; Female; proteiny Drosophily; Male; Drosophila melanogaster; Cell Line; apyrasa; sekvence aminokyselin; Molecular Sequence Data; Amino Acid Sequence; ženské pohlaví; mužské pohlaví